TOURIST ATTRACTIONS AND POSSIBILITIES OF SENTOB VILLAGE IN NAVOI REGION - Olimovich, Rakhimov Sardor (Journal of Learning on History and Social Sciences, 2024)
This article describes the touristic potential and opportunities of the village of Sentob, Navoi region